Does non-implanted electrical stimulation reduce post-stroke urinary or fecal incontinence? A systematic review with meta-analysis. Issue 4 (April 2022) - Cruz, Enrique; Miller, Charne; Zhang, WenWen; Rogers, Kathryn; Lee, Hsiu-Ju; Wells, Yvonne; Cloud, Geoffrey C; Lannin, Natasha A
Background: Urinary and fecal incontinence are disabling impairments after stroke that can be clinically managed with electrical stimulation. Aim: The purpose of this systematic review was to determine the effectiveness of non-implanted electrical stimulation to reduce the severity of post-stroke incontinence. Summary of review: Clinical trials of non-implanted electrical stimulation applied for the purposes of treating post-stroke incontinence were searched in MEDLINE, EMBASE, CINAHL, PEDro, and CENTRAL. From a total of 5043 manuscripts, 10 trials met the eligibility criteria ( n  = 894 subjects). Nine trials reported urinary incontinence severity outcomes enabling meta-analysis of transcutaneous electrical nerve stimulation (TENS; five trials) and electroacupuncture (four trials). Studies provide good-to-fair quality evidence that TENS commenced <3 months post-stroke has a large effect on urinary continence ( SMD  = −3.40, 95% CI −4.46 to −2.34) and a medium effect when commenced >3 months after stroke ( SMD  = −0.67, 95% CI −1.09 to −0.26). Electroacupuncture has a large effect when administered >5 times a week ( SMD  = −2.32, 95% CI −2.96 to −1.68) and a small effect when administered five times a week ( SMD  = −0.44, 95% CI −0.69 to −0.18). Only one trial reported the effect of non-implanted electrical stimulation on post-stroke fecal incontinence. Conclusions: Published trials evaluating the effect of non-implanted electrical stimulation on post-stroke incontinence are few and heterogenous. Synthesized trials suggest that early and frequent treatment using electrical stimulation is probably more effective than sham or no treatment. Further trials measuring incontinence in an objective manner are required.